EPISTEMOLOGI PERSPEKTIF ISLAM DAN BARAT - Budi, Syah (P3M STAIN Sorong, 2016)
Epistemology having relationship with philosophy can be likened to a tree with branches. Philosophical tree has branches in the form of sub-disciplines: philosophy of science, ethics, aesthetics, philosophical anthropology and metaphysics. Epistemology as a branch of philosophy of science is devoted to the sources of knowledge. To arrive at an understanding of Islamic epistemology, it is necessary to approach genetivus subyektivus, which puts Islam as a subject (Islam serve as subject/ benchmark think) and serve as the object epistemology (epistemology be used as a study). Epistemology as a result of the human mind does not intend to interpret Islam, but aims how to acquire knowledge, how the methodology of knowledge, the nature of knowledge and so on related to epistemology. Then by itself the Islamic epistemology are studying Islam itself, or in other words is epistemology according to Islam. The formula makes the difference between Islamic epistemology in general. Islamic epistemology in addition to the general epistemology is concerning revelation as a source of knowledge and inspiration. Epistemology generally assumes that the truth centered on humans because humans have the authority to determine the truth (knowledge). This paper attempts to compare epistemology in the Islamic world and the West.